Egg oral immunotherapy in children (SEICAP I): Daily or weekly desensitization pattern. Issue 1 (21st November 2018) - Martín‐Muñoz, María Flora; Belver, María Teresa; Alonso Lebrero, Elena; Zapatero Remón, Lidia; Fuentes Aparicio, Victoria; Piquer Gibert, Mónica; Plaza, Ana María; Muñoz Román, Candelaria; Martorell‐Calatayud, Cristina; Martorell‐Aragonés, Antonio; Blasco, Cristina; Vilá, Blanca; et al.
Abstract: Background: Studies are required before incorporating egg oral immunotherapy (OIT) into clinical practice. The Spanish Society of Pediatric Allergy, Asthma and Clinical Immunology (SEICAP) conducted a multicenter, randomized controlled study assessing the effectiveness and safety of the OIT using pasteurized egg white (PEW) in egg‐allergic children. Methods: One hundred and one egg‐allergic children (6‐9 years) were randomized for 1 year: 25 to an egg‐free‐diet (CG) and 76 to OIT (target dose 3.3 g PEW proteins), PI (30% weekly plus 5% daily increments) or PII (only 30% weekly increments) buildup patterns. Egg skin prick test, sIgE and sIgG4 serum levels, PEW double‐blind placebo‐controlled food challenge (DBPCFC), and dosing adverse reactions (DARs) were evaluated in all patients from inclusion (T0) until completing 1 year of follow‐up (T12). At T12, egg‐allergic control patients could start OIT. The effectiveness and safety of OIT and the effect of the buildup pattern were analyzed. Results: At T12, 4/25 (16.0%) CG patients passed the PEW DBPCFC vs 64/76 (84.2%) OIT that reached total desensitization ( P = 0.000); 12 egg‐allergic control patients started OIT. Finally, 72/88 (81.81%) patients reached total desensitization, 96.15% PI vs 75.80% on PII ( P = 0.01). Induction period (121.12 ± 91.43, median 98.00 days) was longer in patients on PII buildup pattern, and those with allergic asthma, minor threshold dose, or higher egg sIgE ( P < 0.05). Most patients (89.06%) developed DARs: 74.53% were mild; 21.90% moderate; and 3.5% requiring adrenaline‐treatment. Moderate reactions and those requiring adrenaline were more frequent in patients with allergic asthma, PII pattern, or higher egg sIgE serum antibody levels ( P < 0.05). Conclusions: PEW OIT is an effective treatment for children with persistent egg allergy. A 30% weekly plus 5% daily increment pattern could be more effective and safer than one with only 30% weekly increments.